Oral health indicators as a predictive factor for the quality of life among head and neck cancer patients in Gujarat in India - Parkar Sujal; Sharma Abhishek (Medicinski fakultet i Klinika za stomatologiju, Niš, 2022)
Aim: The aim of this study was to assess the magnitude of various oral health indicators. Further, to identify the oral health indicators as a predictive factor for the quality of life among head and neck cancer patients. Methods: A cross-sectional study was conducted among 400 head and neck cancer patients attending tertiary cancer center. The European Organization for Research and Treatment of Cancer and Head and Neck specific (EORTCQLQH&N35) module was used to assess the patient's quality of life. Oral health indicators (oral hygiene practices, oral complication, dental visits, oral rehabilitation) were recorded through oral examination and personal interviews. Spearman's correlation coefficient was used to assess the correlation between oral health indicators and different scales of QoL. Multivariate linear regression by a backward stepwise method was applied to assess the influence of oral health indicators as a predictive factor for QoL. Results: Out of 400 patients, 54.25% of patients reported having one or another form of oral complication. Periodontal problems were the common oral complication among the patients. There was a weak correlation between oral health indicators and most of the scales of EORTC QLQ-H&N35. Theoretically, linked oral health indicators were found to be significant predictive factors. Conclusion: The results show that there was a high magnitude of poor oral health indicators. Oral health indicators also acted as a significant predictor of quality of life. A multi-disciplinary approach is desirable for the improvement in oral health thus improving the overall quality of life among head and neck cancer patients.